A novel method for assessing the development of speech motor function in toddlers with autism spectrum disorders - Sullivan, Katherine; Sharda, Megha; Greenson, Jessica; Dawson, Geraldine; Singh, Nandini C. (Frontiers in Integrative Neuroscience, 2013)
There is increasing evidence to show that indicators other than socio-cognitive abilities might predict communicative function in Autism Spectrum Disorders (ASD). A potential area of research is the development of speech motor function in toddlers. Utilizing a novel measure called ‘articulatory features’, we assess the abilities of toddlers to produce sounds at different timescales as a metric of their speech motor skills. In the current study, we examined 1) whether speech motor function differed between toddlers with ASD, developmental delay, and typical development; and 2) whether differences in speech motor function are correlated with standard measures of language in toddlers with ASD. Our results revealed significant differences between a subgroup of the ASD population with poor verbal skills, and the other groups for the articulatory features associated with the shortest time scale, namely place of articulation, (p<0.05). We also found significant correlations between articulatory features and language and motor ability as assessed by the Mullen and the Vineland scales for the ASD group. Our findings suggest that articulatory features may be an additional measure of speech motor function that could potentially be useful as an early risk indicator of ASD.